Genetic Algorithm Application for Navigation System on Virtual Shop - Syahputra, Andi Nagoro; Kholimi, Ali Sofyan; Husniah, Lailatul (Universitas Muhammadiyah Malang, 2018)
Online shop becomes one of the updated common types of shop in the era of rapidly grown technology development, yet this system provides its drawbacks. One of the problems which commonly found is a great deal of scamming practices for profit-oriented aims. Virtual shop is defined as a virtual reality application allowing its user to experience shopping in virtual world. A navigation system is required to enable its users in finding out the expected product. Genetic algorithm is one of many search algorithms based on natural selection and natural genetics. On this algorithm, data and string are executed through process of selection to generate problem solving solution. Using this algorithm, the navigation system is proved to be successful on generating path leading to expected product in the virtual shop.